COMMUNICATION AND REFLECTION: PSYCHOANALYSIS AS THE THEME OF A UNIVERSITY STUDY GROUP - Alvarez da Cunha, Isadora Eugenia Euridice [UNESP]; Ramos, Fabio Oliveira; Dias, Murilo Paiotti; Lemes, Claudia Regina; Barja, Paulo Roxo (Univ Vale Paraiba-univap, 2021)
In the second semester of 2018, a group of students and teachers linked (directly or indirectly) to the Psychology graduation course at UNIVAP started to meet weekly to read and discuss texts related to Psychoanalysis. Gradually, the scope of the group entitled Friends of Psychoanalysis (GAP) was expanded, now including students and teachers from other courses and institutions. This article reports the first 30 months of the group's work, presenting the sequence of works covered in this period, as well as the work methodology and systematic of the meetings adopted by the participants, including the necessary adaptation to continue the meetings even during the period of the pandemic. The article also addresses the first works produced by members of the group from the joint studies carried out. Joint learning and its intrinsic relationship with the forms of communication adopted and with the shared and democratic management of GAP are evaluated. Finally, we present the perspectives for the sequence of the group's studies.
Keywords: Instruction; Study group; Psychoaznalysis; University